MANAJEMEN SDM DALAM MEWUJUDKAN LEMBAGA KEUANGAN YANG EFEKTIF - Azriadi Tanjung (Universitas Pahlawan Tuanku Tambusai, 2022)
HR is the key in realizing an effective and efficient organization, therefore the existence of HR is needed in an organization. This study aims to analyze HR management in realizing an effective financial institution. This research uses the literature study method by utilizing authoritative literature sources of books and journals. In order to realize an effective financial institution, three major steps are needed starting from 1) planning carried out with internal-external analysis, SWOT and demand-supply. 2) Recruitment is carried out by identifying hr vacancies and determining the number needed and considering basic competencies. 3) Hr evaluation is carried out with a 360-degree evaluation model that not only involves superiors in evaluating but also involves people who are in their hands. Keywords: Management, HR